-Amylase activity from the entomopathogenic fungus Beauveria bassiana growing in liquid medium - FLÓREZ-M., MARTA CECILIA; LÓPEZ-N., JUAN C.; VALENCIA-JIMÉNEZ, ARNUBIO (Revista Colombiana de Entomología, 2005)
Different isolates of the entomopathogenic fungus Beauveria bassiana were grown using a liquid medium (YPDA / YDA). Under these conditions B. bassiana was able to release an -amylase enzyme into the medium. Using electrophoresis on isoelectric focusing (IEF) gels the isoelectric point (pI) of this amylase activity band was estimated at 6.75 using isoelectric focusing (IEF). Variation in the intensity of enzyme activity was not observed in this band for the different isolates. However, these isolates showed consistent differences in the aamylase activity especially when different concentrations of B. bassiana conidia were used in the culture medium. This is a simple and sensitive method to determine -amylase activity in liquid culture of B. bassiana, which could be used satisfactorily not only to evaluate different fungal entomopathogens, but to make a rapid determination of the possible genetic variants based on the presence or absence of a specific enzyme.